Antimicrobial Efficacy of Biogenic Silver Nanocomposite against Methicillin Resistant Staphylococcus aureus - Chandnani, Y.; Roy, M.; Sannat, C.; Roopali, B.; Roy, S.; Mishra, O. P.; Parveen, K. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted during 2019−2020 to characterize the Carica papaya leaf synthesized silver nanoparticles and to know the MIC of Carica papaya leaf extract along with silver nanoparticles synthesized using Carica papaya leaf extract against MRSA by broth dilution method. Aqueous extract and silver nanoparticles of Carica papaya leaves was prepared using freshly collected disease free leaves. Characterization of C. papaya aqueous leaf extract synthesized silver nanoparticles (CPAgNP) was done by UV-VIS spectra analysis, SEM analysis, Fourier transform infrared (FTIR) analysis and Zeta potential and Particle Size Analysis. A single, strong and broad SPR peak in UV–visible spectrum of the green synthesized silver nanoparticles using the Carica papaya extract was observed at 400 nm. FTIR spectrum revealed the band set at 3465.80 cm-1, 3136.95 cm-1, 2917.61 cm-1, 1625.08 cm-1, 1511.51 cm-1 and 1384.81 cm-1 respectively. Electron microscopy showed that Carica papaya aqueous leaf extract crystalline nanoparticle had definite particle size. The MIC of AECPL against MRSA was found to be 31.25 mg ml-1 while MIC of CPAgNPs against MRSA was found to be 62.5 µg ml-1. MIC of CPAgNPs was reported quite lower as compared to that of AECPL, thus it could be assumed that antibacterial activity of AECPL might potentiate the antibacterial property of Ag-NPs. Therefore, CPAgNPs could be employed as therapeutic agent against bacterial infection.